Ties that bind? Networks and Gender in International Migration - Toma, S (2012)
his thesis examines the roles of migrant networks in the migration and subsequent economic integration of Senegalese men and women in France, Italy and Spain. It challenges the assumption that networks are invariably sources of assistance in the migration process and examines the factors responsible for variations in their influence. In doing so, it uses quantitative methods and analyzes recently collected longitudinal data within the framework of the Migration between Africa and Europe (MAFE) project. Migrant networks -– members of the respondent’s personal circle that have international migration experience – are conceptualized as a form of individual-level social capital that may or may not shape specific outcomes. The thesis contributes to the literature by adopting a longitudinal view of the migration process and considering both migration behaviour and migrants’ labour market trajectories at destination. In doing so, it bridges two areas of research that have mostly developed separately. Second, the intersections between migrant networks and gender, insufficiently studied so far, are here examined in detail. Furthermore, the role of networks in different forms of female mobility – often confounded in previous work - are here analysed separately. Last but not least, the thesis makes a methodological contribution by operationalizing migrant networks in a more dynamic way than previous work. Findings suggest that migrant social capital has a large influence on migration behaviour, while playing a lower and more ambivalent role in migrants’ labour market outcomes at destination. Furthermore, several dimensions are found to shape the extent and channels of networks’ influence. First, men and women do not rely on the same ties in their migration process. Also, women migrating independently of a partner make a different (and greater) use of their migrant connections than those joining their spouse abroad. Migrant social capital is found to work along gender lines: only access to male migrant networks increases the migration likelihood or the job prospects at destination for prospective male migrants. On the other hand, female networks play a crucial role in independent women’s migration process. However, while they greatly increase women’s likelihood of moving to Europe on their own, they also lead them to lower-status jobs. Last, the context of destination was found to shape the operation of migrant networks. In France, where a socio-economically diverse Senegalese community has long been established, pre-migration ties at destination lead to better economic opportunities. In contrast, migrant networks in Italy or Spain appear to channel male migrants into street-selling activities. Thus, bonding social capital in the form of migrant networks appears to reproduce the ethnic niches developed at destination and the gender-segmented nature of the labour market.